Development of Instruments Test to Detect Diabetes Mellitus in Pregnancy - Anissa, Kintan; Rumahorbo, Hotma; Wahyuni, Sri (Universitas Muhammadiyah Semarang, 2023)
Background: Diabetes mellitus in pregnancy is a disorder of carbohydrate tolerance that results in hyperglycemia which is characterized by polyuria, polydipsy, and polyphagia. Pregnant women with DM in pregnancy are associated with high morbidity and mortality. Early detection of DM in pregnancy is important so that further treatment can be done. There is no test instrument that can be used to detect DM in pregnancy. Obtain a test instrument to detect the symptoms of Diabetes Mellitus in pregnancy. Method: The type of research used is R&D (Research and Development). Development research conducted to produce a product in the form of an early detection instrument for diabetes mellitus in pregnancy. The study was conducted by providing early detection instruments for Diabetes Mellitus in pregnancy in first trimester pregnant women and then examining fasting blood sugar in first trimester pregnant women. The number of samples in the study 119 taken by Purposive Sampling technique. Analysis of data using the value of sensitivity, specificity, and accuracy. Result: The test instrument consisted of 13 questions, with a sensitivity value of 72.41%, a specificity value of 91.11%, and an accuracy value of 86.55%.. Conclusion: Early detection instruments for diabetes mellitus in pregnancy can be used as standard guidelines for antenatal care in pregnant women and can be used as an alternative to detect DM in pregnancy before supporting examinations by midwife professionals can be further developed research development using standard methods for measuring blood sugar more accurately and The research was carried out by measuring the precision value so that the instrument produced accurate and consistent results.